2013
DOI: 10.1002/emmm.201302621
|View full text |Cite
|
Sign up to set email alerts
|

VBP15, a novel anti‐inflammatory and membrane‐stabilizer, improves muscular dystrophy without side effects

Abstract: Absence of dystrophin makes skeletal muscle more susceptible to injury, resulting in breaches of the plasma membrane and chronic inflammation in Duchenne muscular dystrophy (DMD). Current management by glucocorticoids has unclear molecular benefits and harsh side effects. It is uncertain whether therapies that avoid hormonal stunting of growth and development, and/or immunosuppression, would be more or less beneficial. Here, we discover an oral drug with mechanisms that provide efficacy through anti-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
235
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 156 publications
(274 citation statements)
references
References 81 publications
(114 reference statements)
16
235
0
Order By: Relevance
“…Both in vitro and in vivo data are consistent with this model. Heier et al (35) have found that the net balance of prednisolone treatment increases muscle strength to normal, but at the same time, it stunts the growth of mice, resulting in lower maximal strength, and increases muscle damage in mdx mice. And Bauer et al (36) have also found that prednisolone increases cardiac fibrosis in mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo data are consistent with this model. Heier et al (35) have found that the net balance of prednisolone treatment increases muscle strength to normal, but at the same time, it stunts the growth of mice, resulting in lower maximal strength, and increases muscle damage in mdx mice. And Bauer et al (36) have also found that prednisolone increases cardiac fibrosis in mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, VBP15, an NF-κB inhibitor with high glucocorticoid receptor specificity, has been designed to reduce the side effects typical of steroids. In mdx mice, the oral administration of VBP15 resulted in improvement of the dystrophic phenotype, with less adverse effects compared with prednisone [18].…”
Section: Corticosteroidsmentioning
confidence: 97%
“…In parallel, novel "dissociative steroids" aim to a broader therapeutic window by separating pharmacodynamic mechanisms responsible for efficacy and side effects. 28,29 Before randomized trial results and innovative treatments become available, natural history studies can provide useful information regarding different GC regimens in DMD.…”
mentioning
confidence: 99%